2018
DOI: 10.20849/ijsn.v3i3.479
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Clinical Practice of Nursing Interns at Tertiary Hospital Jeddah in Saudi Arabia

Abstract: The shortage of nurses in Saudi Arabia like many other countries in the world is a problem. Additionally, there are a unique socio-cultural factor that causes the problem including but not limited to the negative perceptions and attitudes towards nurses. Unfortunately, the apprentices are subjected to a system that is inadequately represented by long working hours, negative images, and work pressures. In addition, several factors are attributed to the problems the students face during the initial year of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Moreover, this study revealed that the nursing interns from some hospitals experienced unfair treatment from other healthcare professionals such as nursing staff and physicians. This finding is consistent with previous studies that have highlighted the unfair treatment and ignorance enacted by nursing preceptors, managers, and physicians towards nursing interns in clinical practice [4]. This finding is likely due to the fact that the nursing staff in the hospitals investigated tended to use the interns to deal with Arabic patients who had difficult personalities and attitudes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, this study revealed that the nursing interns from some hospitals experienced unfair treatment from other healthcare professionals such as nursing staff and physicians. This finding is consistent with previous studies that have highlighted the unfair treatment and ignorance enacted by nursing preceptors, managers, and physicians towards nursing interns in clinical practice [4]. This finding is likely due to the fact that the nursing staff in the hospitals investigated tended to use the interns to deal with Arabic patients who had difficult personalities and attitudes.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were demonstrated in the qualitative study conducted in Saudi Arabia that aimed to explore the factors affecting nursing interns' clinical practice [4]. Data were collected via interviews with undergraduate nursing students doing their internship programme at a tertiary hospital.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations